Extensões de cenários de Branas com defeitos do tipo corda em seis dimensões - Araújo, Júlio César Brasil de (2012)
The purpose of this work is to show an expanse about Gherghetta-Shaposhnikov (GS) scenery through the introduction of a dimensionless parametric in the warped geometry in six dimensions, we suppose which our universe the way that we watch is stood for minkowsk’s 3-brane and the two other are additional dimensions and one of them is compact. In that new model, we are able to achieve the linear process about Einstein’s equation. In order to achieve a perturbation in the metric, so that we are able to locate the equation of motion, consequently finding the massless gravity model. Through these procedures, we have new results about the geometry and physics states in that new scenery. In that new scenery we order the gravity location in a 6-dimensinal geometry, in order to showing an instant where we can find the gravity location, then we get this type of location through an expansion of the GS’s model.